The absorption and translocation of imazaquin in green manures - Flavia Garcia Florido; Patricia Andrea Monquero; Ana Carolina Ribeiro Dias; Valdemar Tornisielo (Acta Scientiarum. Agronomy, 2014)
Green manure species that are tolerant to the herbicide imazaquin can be used in crop rotation schemes that aim to reduce herbicide carryover to sensitive plants such as sunflower or corn. Three different doses of imazaquin (0, 0.15 and 0.28 kgha-1) were applied during the pre-emergence growth stage to Dolichos lablab, Cajanus cajan, Canavalia ensiformis, Crotalaria juncea, C. breviflora, C. spectabilis, Mucuna deeringiana, M. cinerea, M. aterrima, Lupinus albus, Helianthus annuus, Pennisetum glaucum, Avena strigosa and Raphanus sativus, and the results were evaluated in a greenhouse. C. ensiformis and M. cinerea were selected from these species for being the most tolerant, and they were then evaluated for absorption and translocation of 14C-imazaquin in two different growth stages: the cotyledonary stage and the emergence of the first pair of true leaves. M. cinerea individuals showed the best potential for translocating imazaquin to the shoot when compared to C. ensiformes, which accumulated the herbicide mostly in its roots. These plants had a higher ability to accumulate herbicide during their most advanced stage of development, which demonstrates their potential for use in areas that have residual imazaquin.